2022
DOI: 10.1002/admi.202200160
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Lubricative Organic–Inorganic Hybrid Coating with Anti‐Icing and Anti‐Waxing Performances by Grafting Liquid‐Like Polydimethylsiloxane

Abstract: Polydimethylsiloxane (PDMS) is one of the most popular materials to protect infrastructures from the complicated environment due to its chemical stability, nontoxicity, low cost, high durability, and chain flexibility. Herein, a series of organic–inorganic hybrid coatings are prepared by simply grafting loop‐like PDMS on a solid surface. Owning to the low surface energy and high mobility of PDMS chains, the special characteristics, including liquid repellency, anti‐fouling, self‐lubrication, anti‐ and delay‐ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 69 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Self-lubricating PBs can effectively improve the wear resistance in the dry friction state, which is greatly desired in microelectromechanical systems (MEMS). Grafting liquid-like lubrication molecules on the solid surface is an effective way to solve the problem of dry lubrication. , The PDMS molecule is the most popular material used to construct self-lubricating silicon oil PB surfaces because of its chain flexibility. Apart from the self-lubricating performance of the PDMS brush surface, other functions of the PDMS brush surface, such as antiadhesion, , antifouling, , and anti-icing, have also been developed widely. However, the abrasion resistance of the above PDMS brushes is usually neglected, and there is evidence to support that such monolayer PDMS brushes are easily worn under dry friction even when grafted with steady covalent bonds on the surface …”
Section: Hydrophobic Pb Surfacementioning
confidence: 99%
“…Self-lubricating PBs can effectively improve the wear resistance in the dry friction state, which is greatly desired in microelectromechanical systems (MEMS). Grafting liquid-like lubrication molecules on the solid surface is an effective way to solve the problem of dry lubrication. , The PDMS molecule is the most popular material used to construct self-lubricating silicon oil PB surfaces because of its chain flexibility. Apart from the self-lubricating performance of the PDMS brush surface, other functions of the PDMS brush surface, such as antiadhesion, , antifouling, , and anti-icing, have also been developed widely. However, the abrasion resistance of the above PDMS brushes is usually neglected, and there is evidence to support that such monolayer PDMS brushes are easily worn under dry friction even when grafted with steady covalent bonds on the surface …”
Section: Hydrophobic Pb Surfacementioning
confidence: 99%
“…Recently, the flexible polydimethylsiloxane (PDMS) chains were used to prepare SLIPS because of the low cost and hypotoxicity. The PDMS molecules acting as side chains were grafted to main chains and aggregated to form the cores of PDMS chains micelles and then assembled on the coating surface to present excellent slippery and de-icing characteristics. Besides SLIPS, superhydrophobic surfaces were deeply favored by researchers to be anti-icing and de-icing materials because of the intrinsic excellent liquid repellency. , Nevertheless, freezing of moisture in superhydrophobic micro–nano structures in cold damp environments resulted in hydrophobicity reduction. After freezing, the adhesion strength of “Wenzel” ice became large sharply owing to mechanical interlocking, which damaged surface structures and liquid repellency when de-icing by mechanical force.…”
Section: Introductionmentioning
confidence: 99%
“…27−30 This overcomes the limitations of SHSs and SLIPSs; thus, there has been a growing research emphasis on the exploration of liquid- like surfaces. 31−40 Hao et al 35 prepared liquid-like surfaces with excellent stability and durability by grafting the long molecule chain of polydimethylsiloxane on a substrate with covalent bonds. Zhang et al reported a liquid-like ice-shedding coating with extremely low ice adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the micronano structures of SHSs are susceptible to damage, resulting in poor durability. , Another research focus of active anti-icing is the Slippery Liquid-Infused Porous Surfaces (SLIPSs) inspired by pitcher plants. SLIPSs have extremely low ice adhesion strength, which benefits the removal of ice. However, the loss of the SLIPSs lubricants is also an inherent issue, thus limiting their practical application. , Liquid-like surfaces are a type of coating that covalently connects flexible molecular chains or molecular brushes to the surface, without the need to create complex micro- and nanoporous structures. This overcomes the limitations of SHSs and SLIPSs; thus, there has been a growing research emphasis on the exploration of liquid-like surfaces. Hao et al prepared liquid-like surfaces with excellent stability and durability by grafting the long molecule chain of polydimethylsiloxane on a substrate with covalent bonds. Zhang et al reported a liquid-like ice-shedding coating with extremely low ice adhesion .…”
Section: Introductionmentioning
confidence: 99%